UNIVERSITIES AS EXPORTERS OF FINNISH EDUCATION : Experts’ perspectives - Ruuskanen, Henna (My University, 2021)
This master’s thesis investigated universities as exporters of Finnish education from the perspectives of experts. The field of Finnish education export has developed from internationalisation of education in the global world, in which a shift from a welfare society towards a competitive state has evolved. In this study, education export was defined as a knowledge-based business funded by a foreign agent. This study concluded Finnish universities as public, non-profit institutions, which exported products of education and educational knowledge that were traditionally based on equality and free of charge. The research was interested in how Finnish universities in cooperation with other agents exported Finnish education as a profitable business. In this respect, the thesis investigated how experts experienced the cooperation, given the competitive environment, by analysing opportunities, challenges, and problems in the field. Finally, Finnish education export was conceptualised from a theory-driven approach through cultural, social, economic, and symbolic capital. This qualitative research consisted of semi-structured interviews with experts of Finnish education export at four universities in Finland. The interviews were conducted during November and December in 2020, and the data was analysed with a qualitative thematic analysis. The results indicated that cooperation in Finnish education export was arranged in local, regional, and national levels both as (1) commercial profit-oriented business in joint marketing and implementations, trade fair trips, and joint companies, and (2) sharing of good practices and information in networks. Even though cooperation among national education exporters was seen important, limited resources resulted in lack of cooperative arrangements. Moderately perceived, national competition between agents was challenged by international customers. Opportunities of cooperation were increased through visibility, reputation, and risk management. High price level, bureaucratic regulations, and the dual model of the Finnish HEIs set challenges for cooperation. In Finnish education export, the cultural capital of Finnish educational knowledge and Finnishness served as the export product, which was exchanged with the economic capital of the customer. At the same time, the social capital of all parties was increased. Finnish education as an institution was seen as symbolic capital. In the thesis research, the literature and theory of education export are discussed first. Secondly, the methodology and the data of the research are introduced. Thirdly, the data collection is analysed. After that, the findings along with their implications and comparison to previous studies are critically discussed. Lastly, the main results of the study are introduced.
Keywords: International Education, Education Export, Transnational Education, Cross-border Education, Globalisation, Internationalisation of Higher Education